BUSY COMMISSIONERS AND FIRM PERFORMANCE: DO SHARIAH-COMPLIANT FIRMS MATTER? - Rahardjoputri, Rolina; Risfandy, Tastaftiyan; Utami, Ayu Dwi (Bank Indonesia, 2024)
The empirical literature on a one-tier board system has recently focused on busy directors, defined as directors holding multiple similar positions in more than one firm simultaneously. In the same spirit, this paper investigates the impact of busy commissioners (instead of busy directors) on firms' performance for the case of Indonesia, a country adopting a two-tier board system. We find that busy commissioners do not impact accounting performance but are negatively associated with market performance. The markets tend to react negatively to the presence of busy commissioners, while actually the firms are also not advantaged financially by their presence. Interestingly, we also find that Shariah-compliant firms tend to have better accounting performance but not with market performance. Our analysis further reveals that the negative impact of busy commissioners on market performance diminishes in non-Shariah-compliant firms. Perhaps, the different characteristics of Shariah-compliant and non-Shariah-compliant companies, wherein Shariah-compliant firms tend to restrict leverage and cash level, account for the results. These findings are robust across various regressions. This research calls on policymakers to enforce the regulation regarding commissioners to reduce its detrimental impact on performance. The regulators should also collaborate with relevant agencies to educate and promote the existence of Shariah-compliant firms in Indonesia. Acknowledgment The authors would like to thank Universitas Sebelas-Maret, Indonesia, for the partial funding for this study.